Digital Marketing Training Towards Vocational Centers of Excellence: Pelatihan Digital Marketing Menuju SMK Pusat Keunggulan - Rika Septianingsih (Universitas Lancang Kuning, 2023)
PK SMK is one of the government's programs to realize the ideal of educating the nationtion. SMK-PK has a program to develop certain skills and competencies so that the graduates produced are superior and absorbed by the industrial world. The University of Muhammadiyah Riau, as a companion higher education institution (PT), has a program that has been prepared based on the goals and objectives of SMK-PK. Digital marketing is one of eight (8) programs that will be fostered at SMKN-2 Tembilahan. SMKN 2 Tembilahan, one of the SMKs, headed for the Center of Excellence. Digital marketing is important for the business world. along with the development of the